Enterprise Financial Characteristics and Corporate Social Responsibility Costs of Oil and Gas Businesses in Nigeria - Ugbor, Rapheal Oluchukwu; Inyiama , Oliver Ikechukwu; Omodero, Cordelia Onyinyechi; Inyiama, Ethel Chinakpude (Journal of Legal Studies, 2021)
This work evaluated the effect of entity characteristics on company social responsibility costs of oil and gas firms in Nigeria for 2010 - 2019. The independent variables of the study and measures of firm characteristics are total assets, total sales, financial leverage and firm age while the independent variable is corporate social responsibility. A sample of three firms was selected out of a population of eleven oil and gas businesses on the Nigeria Stock Exchange during the period. Supporting data were obtained from the selected firms and analyzed using multiple regression analysis. Findings from the analysis suggest that both total assets and total sales positively and significantly affect the corporate social responsibility costs of the firms. It was also found that financial leverage positively and insignificantly affects the corporate social responsibility costs of the firms. Finding further reveals that firm age negatively and insignificantly affects corporate social responsibility costs of the firms. In the light of the findings, it was recommended that the firm managers should invest in assets especially long-term assets that will yield future streams of returns for their firms. This is because investment in assets improves production and promotes the corporate social responsibility performance of the firms. It was also recommended that the firm managers should promote their products through various product promotion channels as total sales boast firm profitability and promote corporate social responsibility performance. It was further recommended that the firm managers should increase the proportion of debts in their firms’ capital structure. It was finally recommended that firm managers should use a modern approach while implementing their corporate social responsibility programs as opposed to the old style.